Are all CHA2DS2-VASc risk factors created equal? An assessment of stroke risk among 34, 470 patients with CHA2DS2-VASc scores of 1 or 2. (25th November 2020) - Zweibel, S; Passman, R; Sarkar, S; Koehler, J; Ziegler, P
Abstract: Introduction: The CHA2DS2-VASc score is commonly used to assess ischemic stroke risk in patients with documented atrial fibrillation (AF). Whether each combination of CHA2DS2-VASc score 1 or 2 confers a similar stroke risk is poorly understood. Methods: A de-identified database of aggregated electronic health record (EHR) data from 2007–2017 was used to identify patients not on oral anticoagulation (OAC) who had documented AF and CHA2DS2-VASc scores of 1 or 2. CHA2DS2-VASc=1 groups included patients with only heart failure, hypertension, age 65–74, diabetes, vascular disease or female gender. The 17 possible permutations of CHA2DS2-VASc =2 scores were consolidated into 6 groups: prior stroke/TIA, age >75, 2 co-morbidities, 1 co-morbidity + age 65–74, 1 co-morbidity + female gender, or age 65–74 + female gender. Stroke risk hazard ratios were computed for each of these groups. Results: A total of 34, 470 patients (61.0±12.0 years, 67.3% male) not on OAC with a documented history of AF and CHA2DS2-VASc scores of 1 (n=16, 572) or 2 (n=17, 898) were identified. The annual risks of ischemic stroke among CHA2DS2-VASc 1 and 2 patients were 0.22% [0.18–0.26] and 0.38% [0.33–0.43], respectively. For CHA2DS2-VASc =1 patients, age 65–74 conferred a greater risk of stroke while female gender conferred a lower risk. For CHA2DS2-VASc =2 patients, prior stroke/TIA conferred a greater risk of stroke while 1 co-morbidity + female gender conferred a lower risk [Figure]. Conclusion: Ischemic stroke risk varies significantly across specific risk factors in patients with CHA2DS2-VASc scores =1 or 2. Therefore, OAC decisions in these patients should consider individual risk factors rather than the aggregate score alone. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Medtronic